2018
DOI: 10.1097/pec.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Abscess in an Infant Presenting as Fever and Respiratory Distress

Abstract: A 9-month-old healthy female presented during winter to the emergency department with a chief complaint of fever and prominent respiratory symptoms. She was discharged on oseltamivir with a presumptive diagnosis of influenza. She returned to the emergency department 2 days later with continued fever and more upper respiratory symptoms. She was admitted for intravenous hydration to the observation unit with a diagnosis of viral illness (with viral testing that returned positive for adenovirus) and dehydration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 23 Enhanced MRI is still considered the preferred imaging study for confirming the diagnosis of SEA, which is most commonly found in the thoracic region (48%), followed by the lumbar region (31%) and the cervical region. 29 30 31 32 33 As evidenced in Table 1 , the SEA involved multiple vertebral levels; the region of the thoracic vertebrae was affected in 50%, the lumbar region in 50%, and the cervical region in 27.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Enhanced MRI is still considered the preferred imaging study for confirming the diagnosis of SEA, which is most commonly found in the thoracic region (48%), followed by the lumbar region (31%) and the cervical region. 29 30 31 32 33 As evidenced in Table 1 , the SEA involved multiple vertebral levels; the region of the thoracic vertebrae was affected in 50%, the lumbar region in 50%, and the cervical region in 27.7%.…”
Section: Discussionmentioning
confidence: 99%